Determinants of the real exchange rate, misalignment and trade balance in Turkey - Erdal, Fuat (1998)
This study aims to analyse the behaviour of the real exchange rate, to identify the degree of misalignment of the real exchange rate and to investigate its effect on the trade performance in Turkey. Initially the alternative definitions and measurement of the real exchange rate are reviewed. The real exchange rate is defined in terms of relative prices of tradable to nontradable goods. The approaches to modelling the equilibrium real exchange rate are classified as the Purchasing Power Parity models and the relative prices models. Following the latter approach, a structural model is established and then estimated empirically by two alternative cointegration techniques: The Engle and Granger method and the Johansen method. The two methods produce similar results; the real wealth of the private sector, real government expenditures on nontradable goods, external terms of trade and openness of the economy (or alternatively import tariff rate) are identified as the main determinants (fundamentals) of the Turkish equilibrium real exchange rate. Subsequently, an error correction model is estimated to investigate the short-run effects of these factors. The second aim of this study is to measure the degree of misalignment, which is defined as persistent departures of the actual real exchange rate from its equilibrium value. Using the estimates of the cointegration analysis, an equilibrium real exchange rate series is calculated for the sustainable values of the fundamentals, which are approximated by the permanent components of the series, obtained by the Beveridge-Nelson decomposition technique. Then, this is compared with the actual rates in order to construct a misalignment series. The graphical analysis indicates that the misalignment is mainly caused by the policy-induced changes in the actual rates. Finally, the impact of misalignment on the Turkish trade balance is analysed empirically. The results indicate that the trade balance is responsive to the misalignment of the real exchange rate as well as the cyclical government demand for tradable goods. However, the impact of the real wealth is not significant.